Indigenous Remains, Colonialism and Ethical Dilemmas: A Case Study in the Canary Islands - de la Rosa, A. José Farrujia (Journal of Contemporary Archaeology, 2021)
This paper examines how Eurocentric and colonial assumptions that until recently guided the handling of human remains in archaeology and museography are now regarded as problematic, focusing on the situation on the Canary Islands, which has recently passed new legislation (Canary Islands Law 11/2019) on cultural heritage that includes an amendment on human remains. Museums in the Canary Islands continue to display Indigenous bones and embalmed bodies in glass cases, and bone material is even used in contemporary art installations. The paper examines the new law in relation to the ICOM Code of Ethics for Museums as well as other ethical and legal frameworks that address the issue of human remains. We also draw attention to the role of politics, social scientists and society in this debate.